DYNAMIC ANALYSIS OF 6-TPS PARALLEL MECHANISM - GAO XiuLan; ZHANG MinYing; ZHANG FengTao; SHI GeMeng; LU KaiJiang (Jixie qiangdu)
Establish the moving-platform velocity and acceleration relationship between all members and joints of 6-TPS parallel mechanism. The mechanism output speed is used as the independent variable,and set up the mechanism motion differential equations by Kane method. The equation can be used as a dynamic control model and be completely closed loop control of the mechanism. Using matrix norm,derive the perturbation relation of relative variation between the active joint driving force and inertia matrix and the acceleration,put forward the quantitative index of the mechanism acceleration performance and dynamic optimization. Conclude that mechanism acceleration performance indicators is in the singular path limit of the inertia matrix in the working space by an example,and can be used to select the working space of excellent dynamic performance.